Disease Assessment in Behcet Syndrome - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2020)
Behcet syndrome (BS) remains without a diagnostic or laboratory marker, and until recently, there was no measure that would help us in deciding whether the disease was active or responding to treatment. Recently, however, there has been clarification of our thinking about the disease and its sequelae. There are now some measurement tools to assess disease activity in BS. Also, new drugs with much promise are available. We have at hand a handful of fully validated, disease-specific measures for disease activity and quality of life (QoL), and these are widely used. BS starts early in life and may last a long time so that the whole of the working life and the family can be compromised by the disease process. Sometimes, it may burn out in the middle age, but on the other hand, there are some markers of severe disease (starting early, in young men, with eye or thrombotic episodes), which indicate that the prognosis may then be poor. Fluctuant chronic disorders, such as BS, multiple sclerosis, and rheumatoid arthritis (RA), are notoriously difficult for patients and their doctors to manage. Also, in many countries, expensive but more effective drugs will not be an option, which will mean that some patients will not get access to them and that they and their physicians will have to choose whether the expense will be worth the sacrifices to families [1]. Good advice rests on good information, and this itself can rest on the observations from repeated measurement of disease activity using a reliable measure.
Keywords: QUALITY-OF-LIFE; ORAL ULCER ACTIVITY; OUTCOME MEASURES; ACTIVITY FORM; ACTIVITY INDEX; OCULAR ATTACK; FOLLOW-UP; HEALTH; INVOLVEMENT; SEVERITY